EKSPLORASI KEPERCAYAAN NASABAH (CUSTOMER TRUST): DAMPAK PROFESIONALISME SDM DAN TRANSPARANSI SISTEM PEMBAYARAN DIGITAL PADA PROYEK PERUMNAS JAWA TIMUR - Imam Santoso; Yoan Purnamasari Makapuase Bahalau; Zerah Elisa Derek (JURNAL ILMIAH EDUNOMIKA, 2026)
This study investigates the influence of Human Resource (HR) Professionalism and Digital Payment System Transparency on Customer Trust among buyers of Perumnas housing projects in East Java Province. Using a quantitative approach with a survey method, data were collected from 150 respondents who had actively used Perumnas digital payment services. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that HR Professionalism has a significant positive effect on Customer Trust (path coefficient = 0.412, t-statistic = 4.321, p < 0.01), and Digital Payment System Transparency also significantly and positively influences Customer Trust (path coefficient = 0.387, t-statistic = 3.987, p < 0.01). Simultaneously, both variables explain 61.3% of the variance in Customer Trust (R2 = 0.613). The findings suggest that Perumnas East Java should continuously invest in HR capacity development and enhance the transparency of its digital payment platform to strengthen customer confidence in the housing procurement process. Keywords : Customer Trust; Digital Payment; HR Professionalism; Perumnas; Transparency